Allium goumenissanum (Amaryllidaceae), a new species for Bulgaria and new localities in Greece, with additions to the genetic, cytogenetic and morphological characteristics of the species - Vojtěchová, Kateřina; Kobrlová, Lucie; Kitner, Miloslav; Kalous, Roman; Ioannidis, Vassilis; Tzanoudakis, Dimitris; Duchoslav, Martin (Mediterranean Botany, 2024)
Allium sect. Codonoprasum represents an evolutionarily young and rapidly radiating group of bulbous geophytes, with a significant proportion of polyploids and minor morphological differences between species. In the last 20 years, dozens of new species have been described from the Mediterranean. However, very little new information has been obtained on most of them since their description, especially in terms of cytogenetic, molecular and distribution data. Allium goumenissanum is a recently described species of this section, known only from three nearby localities in northern Greece. During the last 10 years, we collected population samples of an unknown species of this section from the southern Balkans, which seemed to be representative of A. goumenissanum. A variety of methods (cytogenetic, molecular, morphological and micromorphological) were used to compare the populations of an unknown species with the morphologically similar species A. goumenissanum and A. stamatiadae. AFLP, ITS sequencing and genome size analyses showed that all populations of the unknown species were in fact A. goumenissanum distinct from A. stamatiadae. The characterization of the morphology and reproduction of A. goumenissanum is completed, and micromorphological and anatomical characteristics of the leaves of both species are newly published. The distribution of A. goumenissanum, based on new data, now includes a more extensive area of north central Greece, and the species is found as a new taxon for Bulgaria.